Implementasi Business Intellegence untuk Menganalisis Hasil Panen dan Produktivitas Padi di Indonesia Menggunakan Tableu - Ahmad Roshid; Fauzi Kurniawan; Intania Widyaningrum; Tasya Rizki Salsabilla; Firman Noor Hasan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2022)
Indonesia is an agricultural country where the majority of the population works in agriculture. Agriculture has an important role in Indonesia in developing the local economy as well as meeting basic human needs. One of Indonesia's largest agricultural products is rice. During the process of collecting data on agricultural products, especially rice, with a large amount of recorded data such as harvested area and annual productivity, it can cause errors in compiling information for the analysis process as well as for evaluation by the ministry of agriculture. Thus, the purpose of this research is to find out how much the harvested area and productivity of rice harvests in Indonesia have increased or decreased. The method used in this article is to process a dataset of harvested area, production, and productivity of rice by province in Indonesia from www.bps.go.id using Tableau. The results of this article are a visualization of a dataset of harvested area and rice productivity by province in Indonesia that can be used for policy making by the ministry of agriculture.